SISTEM INFORMASI UKM E-SPORT UNIVERSITAS HASANUDDIN BERBASIS WEB - Firmansyah; Ramadan, Muhammad Fitrah; Lesmono, Wd. Ananda; Tasrief, Attar Musharih; Pongtambing, Yulita S.; Amran, Rozalina; Sampetoding, Eliyah A. M (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
UKM E-Sport UNHAS is called Electronic Sports Student Activity Unit or commonly E-Sport. E-Sports is the term for video games, with streams of many game genres being played. In order for the student to have easy access to information about her UKM E-Sports, we need a website that can be accessed from any internet-enabled device. The purpose of this study is to design the UKM E-Sport UNHAS website. At the stage of building this sistem, sistem development tools such as data flow diagrams (DFD), context diagrams, entity relationship diagrams (ERD) and flowcharts are used, and PHP and HTML programming languages ​​and MySQL are used as databases. This web-based information sistem design covers many segments of the population. By using the website, visitors from anywhere can see information from this organization. Sport is an important necessity of life that is often underestimated today. Of course, this web-based E-Sports has the specific purpose of raising public awareness that technology is growing.